(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Ovarian cancer remains a leading cause of gynecological cancer-related mortality, with advanced-stage disease (Stage III-IV) often presenting with peritoneal carcinomatosis. Immunohistochemistry (IHC) plays a critical role in characterizing tumor subtypes, guiding treatment decisions, and predicting patient outcomes. This article reviews the current understanding of IHC markers used in ovarian cancer, their prognostic significance, and implications for targeted therapies.